U.S. Congress. Senate. Historical Office oral history interviews - United States. Congress. Senate. Historical Office; Attig, Francis J.; Baker, Richard A.; Ballard, Leonard H.; Caldwell, Charles Sargent, 1932-; Casey, Gregory S., 1953-; Detwiler, Donald J.; Elson, Roy L., 1930-; Ensley, Grover W. (Grover William); Gold, Martin, 1947-; Hallen, Brian, 1939-; Hildenbrand, William F.; et al.
Transcripts of oral history interviews with members and employees of the U.S. Senate conducted by Richard A. Baker, director, and Donald A. Ritchie, associate historian of the Senate Historical Office. Interviewees include Francis J. Attig, Leonard H. Ballard, Charles Sargent Caldwell, Donald J. Detwiler, Roy L. Elson, Grover W. Ensley, Martin Gold, William F. Hildenbrand, Frank Nordy Hoffmann, Pat M. Holt, J. Franklin Little, Carl Milton Marcy, Stewart E. McClure, Roy L. McGhee, Jesse R. Nichols, Scott I. Peek, Warren Featherstone Reid, Floyd Millard Riddick, William A. Ridgely, Dorothye G. Scott, Howard E. Shuman, George A. Smathers, Darrell St. Claire, George Tames, Francis Ralph Valeo, Rein J. Vander Zee, John Robert Vastine, Jerry T. Verkler, Ruth Young Watt, and Francis Orlando Wilcox.
Original recordings retained by the U.S. Senate Historical Office.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Congress. -- Senate -- Interviews; United States. -- Congress. -- Senate -- Officials and employees -- Interviews